Environmental Media in Algeria - Cheurfa , Asma (Journal of Social Sciences and Humanities, 2021)
The term environmental media or media supporting environmental issues reflects the activities and roles that the media can play in the field of environmental conservation in terms of making necessary and necessary changes in the concepts and values associated with environmental behavior through increasing environmental awareness among the public on environmental issues and problems and equipping them with skills and behaviors. Help him to play his role in preserving the environment.